KEWENANGAN LEMBAGA PENJAMIN SIMPANAN DALAM LIKUIDASI BANK - Dasri Librayanti, Ni Made; Mahartayasa, Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
The banking industry shall be consideres as a vital role in restructuring and strengthening national fiscal secto, added to that, to support the national economic growth. In order to mintain the banking stability, Government had established an independent authority which is recognized Indonesia Deposit Insurance Corporation (IDIC). One of its authorities vested shall be settling dispute in the terms of failing bank in the manner of liquidation. One of its legal consequences, resulting from liquidation shall be the Termination of Employment Contract (FLE) towards the employee of the banking service. Goal of this writing shall be the exploration of IDIC authority in the matter of liquidation and its fulfillment of rights due to FLE. Based on that, this writing shall utilize normative legal research by analyzing available laws related to the matter and also related literatures towards the issue. Conclusion drawn from this research shall affirms IDIC authority in overtaking and controlling all aspects of shareholders, including those vested in Annual General Meeting of Shareholders (AGM) . Meanwhile, in the manner of rights fulfillment of the employee due to FLE, shall be salary and alimony.
Keywords: Liquidation, Bank, Indonesia Deposit Insurance Corporation, Labour